STUDIES ON PESTS IN 4 COCONUT CULTIVARS IN LAMPUNG PROVINCE - Wily A. Baringbing; Bariyah Baringbing (International Coconut Community, 1998)
A three‑year field study to investigate species of pests on four (4) coconut cultivars: PB‑1 21, PB‑111, KH17VA‑1 and dwarf Salak, was carried out in Lampung province involving 11 visits from November 1991 to April 1993. Only two regencies: Lampung Utara and Lampung Tengah with 3 and l sub‑districts, respectively were surveyed But only three sub‑districts of Lampung Utara: Sungkai Selatan, Manggala and Mesuji and only Terbanggi Besar in Lampung Tengah were studied Observations of Brontispa longissima Gestro, Plesispa reichei Chapuis, Oryctes rhinoceros Linnaeus, Xylotropus Gideon (Linnaeus), Rhynchophorus vulneratus (Panzer), and the others were studied. Results of the study showed that no cultivars were resistant to any species of pests in Lampung province. There were 19 species of pests, 2 of which do not belong to the insect present in the 2 regencies. The 17 species of insects belong to 4 orders including: Coleoptera, Lepidoptera, Homoptera and Orthoptera in 3, 5, 1 and l families, respectively.